2007
DOI: 10.1007/bf02850007
|View full text |Cite
|
Sign up to set email alerts
|

Acute effect of methylphenidate on QT interval duration and dispersion in children with attention deficit hyperactivity disorder

Abstract: Among childhood psychiatric disorders, attention deficit hyperactivity disorder (ADHD) is of greatest interest to practitioners. Methylphenidate (MPH) is a drug that is widely used in the treatment of children in whom ADHD has been diagnosed. Although this treatment has been used for years, its effects on the heart remain the subject of debate. The QT interval comprises the ventricular activation and recovery periods as seen on electrocardiogram (ECG). The acute effect of MPH on QT interval dispersion is unkno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 18 publications
0
7
0
1
Order By: Relevance
“…Evidence suggests an important role of MPH in cardiovascular system, enhancing widespread tachycardia, changes on vascular pressure and heart rate rhythm (Patrick et al., 1984). In a recent study, Ilgenli et al. (2007) also reported that MPH reduces QT dispersion during the acute period shortly after its administration.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…Evidence suggests an important role of MPH in cardiovascular system, enhancing widespread tachycardia, changes on vascular pressure and heart rate rhythm (Patrick et al., 1984). In a recent study, Ilgenli et al. (2007) also reported that MPH reduces QT dispersion during the acute period shortly after its administration.…”
Section: Resultsmentioning
confidence: 88%
“…Methylphenidate is routinely used for the treatment of ADHD (LeBlanc‐Duchin and Taukulis, 2004). Although this treatment has been used for years, its effects on the heart remain the subject of debate (Ilgenli et al., 2007). Evidence suggests an important role of MPH in cardiovascular system, enhancing widespread tachycardia, changes on vascular pressure and heart rate rhythm (Patrick et al., 1984).…”
Section: Resultsmentioning
confidence: 99%
“…Disrupted dopamine (DA) neurotransmission has been implicated in its pathophysiology (Volkow et al, 2007; Prince, 2008). The stimulants drugs methylphenidate (MP) and amphetamine are the primary medications used to treat ADHD (Ilgenli et al, 2007; Rubia et al, 2009), and both enhance DA signaling in brain (Kuczenski and Segal, 1997), which could account for their therapeutic effects. MP increases DA by blocking dopamine transporters (DATs) and amphetamine by releasing DA from the terminal using the DAT as carrier (Kuczenski and Segal, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the delayed rectifier potassium current (I Kr ) and the action potential duration were unaffected in guinea pigs, 7 and no significant methylphenidate effects on QT interval were seen in studies involving dogs 7 or humans. 8 However, one report has suggested modest increases in heart rate-corrected QT (QTc) intervals in patients prescribed methylphenidate for ADHD. 9 Because drug-induced depolarization and repolarization abnormalities are dose related, 10 it is expected that effects would be more marked in patients with drug overdose.…”
Section: Introductionmentioning
confidence: 99%